The effects of microbial fertilizer based Aspergillus brunneoviolaceus HZ23 on pakchoi growth, soil properties, rhizosphere bacterial community structure, and metabolites in newly reclaimed land - Li, Xuqing; Li, Dingyi; Jiang, Yugen; Xu, Jun; Ren, Xiaoxu; Zhang, Ya; Wang, Hong; Lu, Qiujun; Yan, Jianli; Ahmed, Temoor; Li, Bin; Guo, Kai (Frontiers in Microbiology, 2023)
Introduction Pakchoi is an important leafy vegetable in China. Due to industrialization and urbanization, pakchoi has been cultivated in newly reclaimed mountainous lands in Zhejiang Province, China in recent years. However, immature soil is not suitable for plant growth and needs to be modified by the application of different organic fertilizer or microbial fertilizer based plant-growth-promoting microbe. In 2021, a high efficient plant-growth-promoting fungi (PGPF; Aspergillus brunneoviolaceus HZ23) was obtained from newly reclaimed land of Zhejiang Province, China. In order to valuate microbial fertilizer based A. brunneoviolaceus HZ23 (MF-HZ23) on pakchoi growth in immature soil, we investigated the effect of MF-HZ23 on soil properties, rhizosphere bacterial community structure, and metabolites of pakchoi rhizosphere soil samples. Methods The field experiment (four treatments, MF-HZ23, MF-ZH23 + CCF, CCF and the control) was completely randomly designed and carried out on newly reclaimed land in Yangqingmiao Village of Fuyang district, Hangzhou City, Zhejiang Province, China. In order to evaluate the influence of microbial fertilizer based A. brunneoviolaceus HZ23 on pakchoi in the newly reclaimed land, the number of pakchoi leaves, total fresh and dry weight of the seedlings was counted. In addition, the soil properties, including the pH, OMC, total N, AHN, available P, the genome sequencing, and metabolomics assay were also detected. Results The results revealed a significant difference between MF-HZ23 and the control in soil properties, bacterial community structure, and metabolites. Indeed, compared with the control, MF-HZ23 caused 30.66, 71.43, 47.31, 135.84, and 2099.90% increase in the soil pH, organic matter contents (OMC), total nitrogen (N), alkaline hydrolysis nitrogen (AHN), and available phosphorus (P), respectively. Meanwhile, MF-HZ23 caused 50.78, 317.47, and 34.40% increase in the relative abundance of Proteobacteria, Bacteroidota, and Verrucomicrobiota and 75.55, 23.27, 69.25, 45.88, 53.42, and 72.44% reduction in the relative abundance of Acidobacteriota, Actinobacteriota, Chloroflexi, Planctomycetota, Patescibacteria, and WPS-2, respectively, compared with the control based on 16S amplicon sequencing of soil bacteria. Furthermore, redundancy discriminant analysis (RDA) of bacterial communities and soil properties indicated that the main variables of bacterial communities included available P, AHN, pH, OMC, and total N. In addition, non-targeted metabolomics techniques (UHPLC–MS analysis) revealed that MF-HZ23 resulted in a great change in the kinds of metabolites in the rhizosphere soil. Indeed, in MF-HZ23 and the control group, there were six differentially expressed metabolites (DEMs) belong to organoheterocyclic compounds, organic acids and derivatives, organic nitrogen compounds, and these six DEMs were significantly positively correlated with 23 genus of bacteria, which showed complicated interactions between bacteria and DEMs in pakchoi rhizosphere soil. Conclutions Overall, the results of this study revealed significant modification in physical, chemical, and biological properties of pakchoi soil. Microbial fertilizer based PGPF A. brunneoviolaceus HZ23 (MF-HZ23) can be used as a good amendment for newly reclaimed land.